KREDIBILITAS MICRO INFLUENCER, PEMASARAN BUZZ, DAN CITRA MEREK TERHADAP NIAT BELI PRODUK F&B DI TIKTOK - Thaariq Ayub Arrafah; Fresha Kharisma; Riska Dhenabayu; Ratih Amelia (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the influence of micro-influencer credibility, buzz marketing, and brand image on consumer purchase intention for Food & Beverage (F&B) products on the TikTok platform. This research employs a quantitative approach with an explanatory method and uses purposive sampling to collect data from 150 TikTok users. Data were analyzed using multiple linear regression. The results show that micro-influencer credibility has a positive and significant effect on purchase intention (β = 0.193; t = 2.587; p = 0.011), buzz marketing has the strongest influence (β = 0.404; t = 5.409; p = 0.000), and brand image also significantly affects purchase intention (β = 0.346; t = 4.681; p = 0.000). Simultaneously, the three variables have a significant effect on purchase intention (F = 327.035; p = 0.000). These findings indicate that buzz marketing is the most dominant factor, followed by brand image and micro-influencer credibility. The study concludes that integrating credible micro-influencers, effective buzz marketing strategies, and a strong brand image can significantly enhance consumer purchase intention on TikTok. This research contributes to digital marketing literature and provides practical implications for F&B businesses in designing effective social media marketing strategies